Development of Student Worksheets (E-LKPD) with Game-Based Learning Method Assisted by Liveworksheets on Algebra Material: Pengembangan E-LKPD dengan Metode Pembelajaran Game-Based Learning Berbantuan Livewworksheets pada Materi Aljabar - Tatag Aisyah Fil Miyzaani; Lukman El Hakim; Anny Sovia (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
This study aims to produce a valid and feasible electronic student worksheet (E-LKPD) using a Game-based Learning method assisted by the Liveworksheets application on the material of two-variable linear equation systems. The research method used is developmental research with the ADDIE research model through the stages of analyze, design, develop, implementation, and evaluation. This research was conducted at SMP Negeri 109 Jakarta with data collection techniques in the form of interviews and questionnaires, which were then analyzed using a combination method with an embedded concurrent model. The validity and feasibility of the media can be found in the results of validation and suggestions and comments from expert validators, as well as assessments from teachers and students. The validity and feasibility results from the expert validators were 93.7% (very valid) and media assessments from teachers and students were 90.6% (very feasible). The results of this study indicate that the learning media developed is feasible to be used in school learning.